Study of Bacterial and Phytochemical Contamination in Some Samples of Bottled and Locally Produced Water - Lujain Ebrahim Hussain (Journal of Global Pharma Technology, 2018)
This study was conducted on a number of samples of the most used bottled water found in the governorate markets (Lojin, Thaghir, Sawa, Al Waha, Manar, Rawdatain, Nawar, Al Khaleej, and Albakhera). The samples were between 200 500 and 1500 m The study included detection of total colon bacteria and some physical and chemical properties, namely pH, total dissolved solids, calcium, magnesium, chlorides and sulphates in mg / l unit. The results showed that all samples were acceptable and suitable for using the pylogia, which were within the Iraqi standard of drinking except for the water of the hole where it was polluted (15) colon colony of colon, but globally samples were water oasis and Roumtin and Manar are samples only drinkable, as for the physical and chemical tests were all the characteristics And all samples are acceptable within the Iraqi and international standards for drinking water, but most of the values were greater than mentioned on cans mentioned by the manufacturers.Keywords: Bottled water, Bacteria, Hardness, Sulphate, chloride.